2016
DOI: 10.1165/rcmb.2015-0040oc
|View full text |Cite
|
Sign up to set email alerts
|

Fibrogenic Lung Injury Induces Non–Cell-Autonomous Fibroblast Invasion

Abstract: Pathologic accumulation of fibroblasts in pulmonary fibrosis appears to depend on their invasion through basement membranes and extracellular matrices. Fibroblasts from the fibrotic lungs of patients with idiopathic pulmonary fibrosis (IPF) have been demonstrated to acquire a phenotype characterized by increased cell-autonomous invasion. Here, we investigated whether fibroblast invasion is further stimulated by soluble mediators induced by lung injury. We found that bronchoalveolar lavage fluids from bleomycin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 49 publications
3
19
0
Order By: Relevance
“…There is emerging recognition of the heterogeneity of IPF pathogenesis, including cell-autonomous behavior and chemoinvasive mediators in the local microenvironment (6). This suggests that each individual patient with IPF has numerous factors that contribute to the phenotype of invasive myofibroblasts (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is emerging recognition of the heterogeneity of IPF pathogenesis, including cell-autonomous behavior and chemoinvasive mediators in the local microenvironment (6). This suggests that each individual patient with IPF has numerous factors that contribute to the phenotype of invasive myofibroblasts (30).…”
Section: Discussionmentioning
confidence: 99%
“…Current animal models, primarily those in rodents, have been disappointing (4), and many promising drugs have failed to demonstrate efficacy in human randomized clinical trials. An ideal preclinical model will need to recapitulate the multitude of factors responsible for the disease phenotype or endotype (1,5,6). Furthermore, it would more accurately predict drug responsiveness, while providing new insights into the pathobiology of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…6, B-C) (34). Invading fibroblasts have been shown to be attracted into provisory matrix very effectively by diverse mediators as early as at day 7 after bleomycin challenge (1). Regarding stereological counting, these regions of collapsed alveoli covered by epithelial cells and invaded by cells such as fibroblasts were now counted as one "septal wall" since all structures were engulfed in the tissue underneath an epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…A feature of fibroblasts in pulmonary fibrosis is the ability to invade through basement membranes and ECM, and emerging studies demonstrate that IPF lung fibroblasts can be distinguished from normal lung fibroblasts by their acquisition of an invasive phenotype [104107]. One study showed the lung fibroblasts from mice that are deficient in β-arrestin, which are protected from bleomycin-induced lung fibrosis, migrate normally but have an impaired ability to invade into Matrigel [105].…”
Section: Fibrotic Lung Mesenchymal Cells and The Hallmarks Of Cancermentioning
confidence: 99%
“…Stimulation of TLR9 significantly increased fibroblast expression of CD44 and matrix metalloproteinase-14 while promoting invasion into Matrigel [109]. Finally, a recent study indicates that while fibrotic lung fibroblasts have increased invasiveness at baseline, they also have an amplified invasive response to bronchoalveolar lavage fluid obtained from fibrotic lungs [107]. These studies demonstrate that local invasion of fibroblasts through basement membrane and interstitium can contribute to the pathogenesis of lung fibrosis, including IPF.…”
Section: Fibrotic Lung Mesenchymal Cells and The Hallmarks Of Cancermentioning
confidence: 99%